Caffeine's Effects on Consumer Spending. (March 2023) - Biswas, Dipayan; Hartmann, Patrick; Eisend, Martin; Szocs, Courtney; Jochims, Bruna; Apaolaza, Vanessa; Hermann, Erik; López, Cristina M.; Borges, Adilson
Caffeine is the world's most popular stimulant and is consumed daily by a significant portion of the world's population through coffee, tea, soda, and energy drinks. Consumers often shop online and in physical stores immediately after or while consuming caffeine. This is further facilitated by the increasing prevalence of coffee shops and by the phenomenon of some retail stores having in-store coffee bars and offering complimentary caffeinated beverages. This research examines how caffeine consumption before shopping influences purchase behavior. The results of a series of experiments conducted in the field (at multiple retail stores across different countries) and in the lab show that consuming a caffeinated (vs. noncaffeinated) beverage before shopping enhances impulsivity in terms of more items purchased and higher spending. This effect is stronger for "high-hedonic" products and attenuated for "low-hedonic" products. These findings are important for managers to understand how a seemingly unrelated behavior (i.e., caffeine consumption) in and/or around the store affects spending. From a consumer perspective, although moderate amounts of caffeine consumption can have positive health benefits, there can be unintended negative financial consequences of caffeine intake on spending. Thus, consumers trying to control impulsive spending should avoid consuming caffeinated beverages before shopping.